2023
DOI: 10.1111/jpi.12869
|View full text |Cite
|
Sign up to set email alerts
|

BPS‐induced ovarian dysfunction: Protective actions of melatonin via modulation of SIRT‐1/Nrf2/NFĸB and IR/PI3K/pAkt/GLUT‐4 expressions in adult golden hamster

Abstract: Ever‐increasing occurrence of plastic‐manufacturing industries leads to environmental pollution that has been associated with declined human health and increased incidence of compromised reproductive health. Female subfertility/infertility is a complex phenomenon and environmental toxicants as well as lifestyle factors have a crucial role to play. Bisphenol S (BPS) was believed to be a “safer” replacement of bisphenol A (BPA) but recent data documented its neurotoxic, hepatotoxic, nephrotoxic, and reprotoxic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…This indicated that SIRT1, as an upstream signaling molecule, was involved in the regulation of Nrf2 by F 2 , which was consistent with recent reports. [36][37][38] These results confirmed that F 2 could alleviate oxidative damage through SIRT1/Nrf2 signaling pathway.…”
Section: Discussionsupporting
confidence: 63%
“…This indicated that SIRT1, as an upstream signaling molecule, was involved in the regulation of Nrf2 by F 2 , which was consistent with recent reports. [36][37][38] These results confirmed that F 2 could alleviate oxidative damage through SIRT1/Nrf2 signaling pathway.…”
Section: Discussionsupporting
confidence: 63%
“…and anti‐inflammatory cytokines (IL‐10, IL‐4, IL‐12, etc.). 45 , 46 The relative or absolute deficiency of growth factors and the decrease in their receptor activity are important pathophysiological foundations that lead to difficult wound healing. 47 The transformation of macrophages from M1 to M2 is supposed to be highly beneficial for wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…However, research has shown that BPS had detrimental effects on ovarian function and reduced the expression of Nrf2, similar to the effects observed with BPA. What is more, these were rescued via melatonin via the modulation of the SIRT-1/Nrf2/NF-κB pathway [60].…”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 98%